UXL encyclopedia of world biography - Tyle, Laura B. (Detroit : UXL, 2003)
A collection of 750 biographies and portraits of notable historic and current figures in American and world history, literature, science and math, arts and entertainment, and the social sciences
v. 1. A-Ba -- v. 2. Be-Cap -- v. 3. Car-Da -- v. 4. De-Ga -- v. 5. Ge-I -- v. 6. J-L -- v. 7. M-Ne -- v. 8. Ni-Re -- v. 9. Rh-S -- v. 10. T-Z.
Each volume includes the cumulative index
Includes bibliographical references
Keywords: Biography -- Dictionaries -- Juvenile literature; Biography -- Dictionaries